Proceedings of the International Conference on Science and Technology (ICOSAT 2017) 2018
DOI: 10.2991/icosat-17.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Gemstone Type Identification System Based on HSV Space Colour Using an Artificial Neural Network Back Propagation Algorithm

Abstract: A gemstone is a mineral stone that be formed from the result of geological processes and has a hardness above 7 Mohs. Nowadays, gemstones have become famous in Indonesian society. Many facts concerning the business of gemstone rings, including encouragement by the the central government for the gemstone souvenirs that are given to State guests by the President of Indonesia, gemstone contests and gemstone exhibitions have all contributed to pique the interest of researchers in the subject. This current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Stacking Support Vector Machine, Logistic Regression and Multilayer Perceptron models further improved the accuracy by 0.3%. Despite the robustness of computer vision systems in mineral recognition, only one study on automatic identification of gemstone images [30] has been reported to date, to the best of the authors' knowledge. A per-class accuracy of 75-100% was attained for classifying unseen Ruby, Blue Sapphire and Emerald images based on the Hue channel of the HSV colour space using an Artificial Neural Network.…”
Section: Introductionmentioning
confidence: 99%
“…Stacking Support Vector Machine, Logistic Regression and Multilayer Perceptron models further improved the accuracy by 0.3%. Despite the robustness of computer vision systems in mineral recognition, only one study on automatic identification of gemstone images [30] has been reported to date, to the best of the authors' knowledge. A per-class accuracy of 75-100% was attained for classifying unseen Ruby, Blue Sapphire and Emerald images based on the Hue channel of the HSV colour space using an Artificial Neural Network.…”
Section: Introductionmentioning
confidence: 99%